A phono-ethnic story of Nigerian English: As told by high vowels. (2019) - Isiaka, Adeiza Lasisi
Abstract: This study explores the role of dialect-contact among developing L2 phonologies, and the influence of L1 ± ATR system on L2 English tense/lax vowels, using the under-documented Ebira English spoken in Nigeria as an exemplar. The variety presents an interesting precedent due to its differential historical contact with Yoruba English, starting in the early colonial periods, and Hausa English, becoming more prominent in the past three decades. This is relevant because the two dialects differ in degree of acoustic distinction of the tense-lax high vowel pairs, with Yoruba English being reported as having a merger, and Hausa English reported as having differentiation. Framed by theories of L2 speech and evolutionary approaches to language change, sociophonetic procedures are deployed to measure the high front and back vowels in Ebira English, as well as assess the trajectory of sociolinguistic variation within the variety. If it is the case that increased contact with Hausa English in the past three decades is influencing Ebira English vowels, a shift in apparent time away from merger and towards distinction would be expected. This would also be the case if the ± ATR distinction in Ebira have substrate effects on the realisation of English tense/lax vowels. The evidence of contrast between the high front (FLEECE & KIT) and back (GOOSE & FOOT) vowels thus confirm these predictions, while variation in the system is further indicated by gender and linguistic contexts. Highlights: Distinction between KIT & FLEECE and GOOSE & FOOT is supported for the variety. Contrast between FLEECE and KIT may have either been influenced by Ebira L1 ± ATR system or the Hausa English variety. The front high vowels are stable in apparent time, while younger speakers are leading in the fronting of the high back vowels. In regard to sociolinguistic variation, contrast between the high front vowels is gender-driven (led by female speakers). Contrast between GOOSE & FOOT appears influenced by mainly contact with the Hausa English accent.